Bibliometric Analysis of Research Trends on Economic Decoupling: Insights from 2010 to 2025 - Judijanto, Loso; Apriyanto, Apriyanto (The Es Economics and Entrepreneurship, 2025)
This study presents a comprehensive bibliometric analysis of global research trends on economic decoupling between 2010 and 2025. Drawing on 647 documents indexed in the Scopus database, the analysis maps the intellectual structure, thematic evolution, and collaborative networks shaping the field. Using VOSviewer, the study visualizes co-authorship patterns, keyword co-occurrences, temporal trends, and density of thematic concentration. Results indicate that research on decoupling has transitioned from abstract debates around economic growth and environmental limits toward empirical, policy-relevant studies focused on carbon emissions, decomposition analysis, and sustainable development strategies. China, the United States, and Germany emerge as dominant contributors, with rising global collaboration. The keyword overlay reveals an increasing shift toward themes like circular economy and renewable energy in recent years. The study contributes to the theoretical consolidation of the field while offering practical insights for policymakers and researchers to align future efforts with global sustainability goals. Limitations include reliance on a single database and the interpretive boundaries of bibliometric tools.